PERAN GURU PAI DALAM MENINGKATKAN KUALITAS BERAGAMA SISWA DI SMK NURUL HIDAYAH AL FALAH PUNGGING MOJOKERTO - Muslih, Imam (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article describes the role of PAI teachers in improving the religious quality of students at SMK Nurul Hidayah Al Falah Pungging Village, Mojokerto Regency. With a qualitative descriptive approach, the data collection techniques use observation, interviews, and documentation, the researcher analyzed by the Miles and Hubberman analysis techniques, data reduction, data display, and conclusion, the research gave results that the quality of religious students, can be seen from everyday morals, both in terms of speech, behavior, and character towards teachers and friends. Honesty which is the principle of faithful people reflected in everyday school life. Through habituation activities, the role of PAI teachers is to oversee the program and make these activities a good habit which includes scheduled/routine, spontaneous, and caring activities. The role of PAI teachers in habituation activities can be seen from the results of students' behavior and responses to programs/activities related to improving the religious quality of students from time to time. SMK Nurul Hidayah Al Falah Pungging has adequate facilities and infrastructure to support the program, but external factors often become obstacles, especially the freedom of students to access the internet, especially outside school hours. PAI teachers make an effort, one of them is to approach emotionally, habituate in religious activities and become a good example for students in the SMK Nurul Hidayah Al Falah Pungging, until the efforts made are in accordance with what is expected Keywords: PAI Teacher's role, habituation, religious quality